Irene “Renie” A. Bierman-McKinney - Jere L. Bacharach (Al-'Usur al-Wusta, 2015)
Writing obituary notes is an expectation when one is as senior as I am, but when the subject is your closest friend for three and a half decades, your intellectual mentor, and your collaborator on a wide range of projects the task is very hard, very sad but necessary. This is the case for me in preparing what follows.